Two new species of Pseudotelorchis (Digenea, Telorchiidae), parasites of the Caiman, Caiman crocodilus yacare (Reptilia, Crocodylia) from the Pantanal Mato-Grossense, Brazil - Joäo B. Catto; J. F. R. Amato (Memorias do Instituto Oswaldo Cruz, 1993)
Pseudotelorchis caimanis n. sp. and P. yacarei n. sp. are described based on specimens collected from Caiman crocodilus yacare (Daudin) in the Pantanal Mato-grossense, Brazil. This is the first record of any species of Telorchiidae Stunkard, 1924, parasitizing crocodilians. Pseudotelorchis caimanis n. sp. differs from P. comapactus, the only species described in the genus with seminal receptacle, testes in tandem, and genital pore lateral to acetabulum. Pseudotelorchis yacarei n. sp. differs from the two other species for its body shape, for infecting the intestine instead of the uterus, by having regularly disposed instead of irregulary disposed uterine loops, and by having the vitelline glands disposed in longitudinal lateral lines instead of in lateral bunches.